CHARACTERIZATION OF MALAYSIAN JATROPHA SEED OIL USING FTIR AND GCMS - Mathanraj Jayagobi; Amni Haslinda Alpandi; Hazlina Husin (Platform, a Journal of Engineering, 2021)
Flow assurance problems such as wax deposition impacted the oil and gas industry in various points of oil transport hence a cure is widely researched. This paper aims to establish a cure by using Jatropha curcas seed oil (non-edible) originated from Malaysia and its sustainability as a wax inhibitor component. Extraction and characterization of Jatropha seed oil using Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography-Mass Spectrometry (GCMS) were conducted to identify the properties of Jatropha seed oil such as the presence of oleic acid which is the main component required in wax inhibitor. Jatropha seed oil extraction was conducted using a soxhlet extractor and n-Hexane solvent which was heated at 70°C. The obtained results illustrated that at the peak of 1746.48 cm–1, FTIR analysis indicated the presence of C=O stretching carboxyl which was the ester fatty acid group while at a retention time of 36.834 min, 44.91% of the oleic acid was present via GCMS analysis. The analysis revealed the presence of high oleic acid in Jatropha seed oil has great potential as wax inhibitor to improve the flowability retarded by wax precipitation.